2009
DOI: 10.1007/s11483-009-9143-6
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Selected Boletus Mushrooms

Abstract: Considering the growing interest for mushrooms and the demand search of natural antioxidants sources, the aim of this study was to investigate the antioxidant properties of two edible widely used Boletus species, Boletus edulis, and Boletus auranticus, collected from Istra region in Croatia in late summer 2007. To evaluate the antioxidant properties and content of antioxidant compounds, scavenging capacity on DPPH˙, OH˙, and O 2˙− radicals, reducing power and capacity to inhibit lipid peroxidation has been inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 53 publications
1
38
4
2
Order By: Relevance
“…For example at the concentration of 0.2 mg/ml measured absorbance of ascorbic acid was 1.192±0.03, while for D. confragosa was 0.442±0.06. However, the reducing power of the investigated mushroom extract was higher than the previously reported reducing power for mushroom Boletus edulis and Boletus aurantiacus (0.223 and 0.192, respectively) [30] and also for the reported reducing powers of the methanolic extracts of Dictyophora indusiata, Grifola frondosa, Hericium erinaceus and Tricholoma giganteus [31]. This property suggests that D. confragosa extracts may act as free radical chain terminators, transforming reactive free radical species into more stable non-radical products.…”
Section: Antioxidant Activitycontrasting
confidence: 79%
See 2 more Smart Citations
“…For example at the concentration of 0.2 mg/ml measured absorbance of ascorbic acid was 1.192±0.03, while for D. confragosa was 0.442±0.06. However, the reducing power of the investigated mushroom extract was higher than the previously reported reducing power for mushroom Boletus edulis and Boletus aurantiacus (0.223 and 0.192, respectively) [30] and also for the reported reducing powers of the methanolic extracts of Dictyophora indusiata, Grifola frondosa, Hericium erinaceus and Tricholoma giganteus [31]. This property suggests that D. confragosa extracts may act as free radical chain terminators, transforming reactive free radical species into more stable non-radical products.…”
Section: Antioxidant Activitycontrasting
confidence: 79%
“…The radical scavenging activity was found to exhibit 50% of the inhibition value (IC 50 value) at the extract concentration of 0.015±0.007 mg/ml for the investigated D. confragosa extract. The calculated IC 50 value was slightly lower than the reported IC 50 value for Boletus edulis (0.016±0.003 mg/ml) and lower than the reported value for Boletus aurantiacus (0.024±0.004 mg/ml) dry extract [30], or methanolic extract of Ganoderma tsugae, known as Ling chic (0.25±0.0016 mg/ml) [34], which indicated a higher antioxidant activity in comparison to the reported values.…”
Section: Antioxidant Activitycontrasting
confidence: 72%
See 1 more Smart Citation
“…There are several reports on antioxidant activity of B. edulis and A. campestris (Vidović et al, 2010;Kosanić et al, 2012;Woldegiorgis et al, 2014) by using other extraction solvents. In this study, the antioxidant capacity of selected mushrooms was confirmed by methanol extracts.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of mushrooms and their extracts antioxidant activity and the content of antioxidant compounds is very actual scientific subject [2]. The antioxidant activity of some mushrooms extracts were also studied by other researchers.…”
Section: Introductionmentioning
confidence: 99%